Does culture affect divorce decisions? Evidence from European immigrants in the US - Delia Furtado; Miriam Marcén; Almudena Sevilla-Sanz (Institute for the Study of Labor (IZA), 2011)
This paper explores the role of culture in determining divorce decisions by examining country of origin differences in divorce rates of immigrants in the United States. Because childhood-arriving immigrants are all exposed to a common set of US laws and institutions, we interpret relationships between their divorce tendencies and home country divorce rates as evidence of the effect of culture. Our results are robust to controlling for several home country variables including average church attendance and GDP. Moreover, specifications with country of origin fixed effects suggest that divorce probabilities are especially low for immigrants from countries with low divorce rates that reside amidst a large number of co-ethnics. Supplemental analyses indicate that divorce culture has a stronger impact on the divorce decisions of females than of males pointing to a potentially gendered nature of divorce taboos.
urn:nbn:de:101:1-201109297590
Keywords: J12; Z13; J61; 330; divorce; culture; immigrants; Einwanderung; Kultur; Scheidung; Europa; USA